CREATING TELEGRAM BOTS WITH JAVASCRIPT - J.J. Munirov (Recent scientific discoveries and methodological research, 2025)
This article explores the process and tools for creating Telegram bots using JavaScript. It discusses the basics of the Telegram Bot API, popular JavaScript libraries like node-telegram-bot-api, and the typical development workflow. The benefits and potential challenges of implementing Telegram bots in various applications are also highlighted. Finally, the article looks at how these bots can be customized and scaled to meet the growing demands of users and businesses.